In Vitro Propagation of Globba annamensis Gagnep. for Conservation of Rare Plant Species in Thailand - นนทะลี สุกัญญา; แสนสุข สุรพล; แสนสุข ปิยะพร (KKU Science Journal, 2017)
Globba annamensis Gagnep. Has an ornamental potential. It was rarely found in natural habitat. The status of this plant is rare species. In vitro propagation of G. annamensis by tissue culture technique was investigated. Microshoots of G. annamensis (1 cm in length) were cultured on Murashige and Skoog (MS) (1962) medium supplemented with various concentrations (0, 0.5, 1, 2, 3, 4, 5 and 6 mg/l) of cytokinin hormone (BA, TDZ and Kinetin), different concentrations (0, 0.1, 0.5 and 1 mg/l) of auxin hormone (IBA, IAA and NAA), and 0, 0.5, 1, 2, 3, 4 and 5 mg/l of BA and TDZ in combination with 1 mg/l of NAA for eight weeks to induce shoot and root formation. The microshoots of G. annamensis cultured on MS medium supplemented with 3 mg/l TDZ produced the maximum number of shoots (5.33 shoots per explant) and the maximum number of root was observed in the MS medium supplemented with 4 mg/l BA and 1 mg/l NAA (21.50 roots per explant).